1993
DOI: 10.1080/00268979300101311
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum UV fluorescence excitation spectroscopy of BCl3in the range 35–140 nm

Abstract: Fluorescence excitation spectra of BC13 have been recorded in the range 35-140 nm (9-35 eV) using synchrotron radiation. Both resonant and non-resonant peaks are observed corresponding to neutral fragment (i.e. BC12) and parent ion (i.e. BC1 +) emission. BC12 emission results from dissociation of low-lying Rydberg states of BC13 in the energy range 9-12 eV, and at least two electronic transitions in BC12 are observed. One (in the range 400-650 nm) originates from dissociation of the 3s and 3p Rydberg states, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The close similarity between the photoabsorption and fluorescence excitation spectra suggests that dissociation to form excited emitting states of the BBr~ radical is a major decay pathway for these BBr 3 Rydberg states. The spectra are considerably more complicated than the equivalent fluorescence excitation spectra of either BF 3 or BCI a [1][2][3]. Planckaert et al attribute much of the additional structure to transitions to triplet Rydberg states which become weakly allowed because of the relatively large spin-orbit coupling interaction due to the bromine atoms.…”
Section: Non-dispersed Fluorescence and Dispersed Emission Spectroscomentioning
confidence: 97%
See 2 more Smart Citations
“…The close similarity between the photoabsorption and fluorescence excitation spectra suggests that dissociation to form excited emitting states of the BBr~ radical is a major decay pathway for these BBr 3 Rydberg states. The spectra are considerably more complicated than the equivalent fluorescence excitation spectra of either BF 3 or BCI a [1][2][3]. Planckaert et al attribute much of the additional structure to transitions to triplet Rydberg states which become weakly allowed because of the relatively large spin-orbit coupling interaction due to the bromine atoms.…”
Section: Non-dispersed Fluorescence and Dispersed Emission Spectroscomentioning
confidence: 97%
“…The experiments described form part of a series of studies of the fluorescence excitation spectroscopy of the group III halides [1][2][3]. The boron trihalides, BF3, BCI~ and BBr3, are widely used in the radiofrequency plasma etching of semiconductor devices [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoelectron spectroscopic studies of Bassett and Lloyd 3 are consistent with the photoionization observations. Tuckett and coworkers studied the fluorescence excitation spectroscopy 4,5 and fragmentation pattern 6 of BCl 3 . They found that when BCl 3 is excited in the 9-12 eV energy range the fluorescence is dominated by BCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…29 A number of experimental studies contribute to an understanding of the molecular and electronic structure of the BCl 3 molecule. These include electron-impact excitation and ionization, [31][32][33] negative-ion formation, [31][32][33][34][35][36][37] electron-impact dissociation into excited fragments, [38][39][40] photoelectron spectra, 28,41,42 photoionization and photodissociation, [43][44][45][46][47][48][49] and photoabsorption and fluorescence measurements in the ultraviolet/visible ͑UV/VIS͒ region. 44 -52 Some of the photophysical studies incorporated mass analysis and fluorescence measurements and established the fragmentation patterns of BCl 3 at specific photon wavelengths ͑see Sec.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 99%